1999
DOI: 10.1021/np990085l
|View full text |Cite
|
Sign up to set email alerts
|

Two New Alkaloids from Artabotrys uncinatus

Abstract: A novel oxazoloaporphine, artabonatine A (1), and a new 7-hydroxyaporphine, artabonatine B (2), have been isolated and characterized from the fresh unripe fruits of Artabotrys uncinatus, along with five known compounds. Structure elucidation of 1 and 2 was based on UV, IR, NMR, and MS analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 12 publications
0
55
0
Order By: Relevance
“…In addition to benzylisoquinoline alkaloids 1-3, 10 other known aporphinoid alkaloids were isolated and identified as norisocorydine (4) (Haynes et al, 1966), nornuciferine (5) (Shakirov et al, 1996), stepharine (6) (Haynes et al, 1966), isocorydine (7) (Shakirov et al, 1996), anonaine (8) (Sette et al, 2000), roemerine (9) (Sette et al, 2000), liriodenine (10) (Costa et al, 2011), atherospermidine (11) (Costa et al, 2011), laureline (12) (Roblot et al, 1983), artabonatine B (13) (Hsieh et al, 1999), by comparing the experimental and reported physical data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to benzylisoquinoline alkaloids 1-3, 10 other known aporphinoid alkaloids were isolated and identified as norisocorydine (4) (Haynes et al, 1966), nornuciferine (5) (Shakirov et al, 1996), stepharine (6) (Haynes et al, 1966), isocorydine (7) (Shakirov et al, 1996), anonaine (8) (Sette et al, 2000), roemerine (9) (Sette et al, 2000), liriodenine (10) (Costa et al, 2011), atherospermidine (11) (Costa et al, 2011), laureline (12) (Roblot et al, 1983), artabonatine B (13) (Hsieh et al, 1999), by comparing the experimental and reported physical data.…”
Section: Resultsmentioning
confidence: 99%
“…As a Chinese traditional folk medicine, its roots and fruits are used for treating malaria and scrofula, respectively (Radloff et al, 1996;Chatrou et al, 2004;Nicolaou et al, 1994). Previous chemical studies on this genus have led to the isolation of an array of compounds including compounds classified as bisabolene (Liang et al, 1979;Zhang et al, 1988) and guaiane sesquiterpenes (Fleischer et al, 1997), steroids (Hasan et al, 1987), aporphine (Eloumi-Ropivia et al, 1985;Wu et al, 1989;Guinaudeau et al, 1994;Wijeratne et al, 1995;Hsieh et al, 1999) and tetrahydroberberine (Cave et al, 1986) alkaloids, long chain hydrocarbons (Jain et al, 1998), and flavonoid glycosides . Earlier chemical and pharmacological studies had showed that its sesquiterpenes and alkaloids account for the antimalaria and antitumor activities, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Ylang-Ylang oil is used in the food industry as the fl avoring ingredient. It is approved as a food additive by Food and Drug Administration.…”
mentioning
confidence: 99%
“…and A. hexapetalus (L. f.) Bhandari) of the family of Annonaceae is a shrub distributed in tropical and temperate Asia from the southern part of China to India. The roots and fruits of the plant are being used for the treatment of malaria and scrofula in traditional Chinese medicine [2]. Previous phytochemical studies of the plant have yielded aliphatic alcohols and esters [3] [4], a long chain alkylated amethylene-g-butyrolactone [5], sesquiterpenes [6], alkaloids [7] [8], and anthraquinones [9].…”
mentioning
confidence: 99%